Pengambilan Keputusan, Sikap dan Hubungan antara Karakteristik dengan Sikap Konsumen Minuman Kopi Benefit Coffee Kota Bandar Lampung - Rianti, Anissa Indah; Indriani, Yaktiworo; Adawiyah, Rabiatul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This consumer behavior research aims to determine decision making, attitudes and the relationship between characteristics and attitudes of coffee beverage consumers at Benefit Coffee (BC) using the survey method and involving 68 respondents. Data collectioniwas carriedi out in February 2025 and analyzed descriptively and quantitatively using the Fishbein multiattribute model and Spearman Rank correlation test. The results showed that the main purpose of visiting BC was to find a place to relax, with consumer motivation to try various flavors of BC coffee. Consumers obtain product information through friend recommendations that influence their decision to try. Consumer attitude whenithe desired product runsi out is to choose another flavor as an alternative. Consumers tend to plan purchases with the main consideration of coffee flavor. Most consumers are satisfied and interested in making repeat purchases. Consumer attitudes towards BC coffee drinks fall into the moderately good category.  There is a significant relationship  between age and incomei of consumers and consumeri attitudes towards BC coffee drinks.